PANDEMIC ERA: THE ROLE OF PARENTS AT HOME IN THE OCCURRENCE OF MODULAR DISTANCE LEARNING - Idulog, Mark Vergel (International Journal of Arts, Sciences and Education, 2022)
Due to the COVID-19 outbreak, education was interrupted. To continue offering high-quality education led to a dramatic transition away from face-to-face instruction and to blended learning. However, modular distance learning, as one of the adaptable learning modes, was chosen by most parents. Hence, this study seeks to determine the role of parents in the effectiveness of modular distance learning during the COVID-19 pandemic era, ascertain whether there is a relationship between the parents’ roles and their backgrounds, determine whether there is a relationship between the parents’ backgrounds and the children’s academic performance and determine whether the child’s educational performance was related to the role of the parents. A survey questionnaire was used to acquire information on the parents’ profiles and the role they played or did not play. Mean, frequency count, and Spearman correlation were used to analyze the data. Results showed a relationship between parents’ profiles and roles in their child’s academic achievement. The children’s academic performance in modular distance learning is boosted, mainly if the parents work and earn a higher income. Modular distance learning is effective when parents act as friendly teachers and motivators for their children and are employed in either public or private agencies.